Burnout, psychological morbidity, job stress, and job satisfaction in Chinese neurologists. (2nd May 2017) - Zhou, Xinyu; Pu, Juncai; Zhong, Xiaoni; Zhu, Dan; Yin, Dinghong; Yang, Lining; Zhang, Yuqing; Fu, Yuying; Wang, Haiyang; Xie, Peng
Abstract : Objective: To investigate the prevalence of and personal and professional characteristics associated with burnout, psychological morbidity, job stress, and job satisfaction in Chinese neurologists. Methods: The China Neurologist Association conducted a national cross-sectional study from September 2014 to March 2015. A questionnaire including the Maslach Burnout Inventory, the 12-item General Health Questionnaire, the Consultants' Mental Health Questionnaire, and questions assessing personal and professional characteristics, career satisfaction, and current doctor-patient relationships was administered. Results: A total of 693 directors of neurology departments and 6, 111 neurologists in 30 Chinese provinces returned surveys. Overall, 53.2% of responding neurologists experienced burnout, 37.8% had psychological morbidity, 50.7% had high levels of job stress, 25.7% had low levels of job satisfaction, 76.9% had poor doctor-patient relationships, and 58.1% regretted becoming a doctor. Factors independently associated with burnout were lower income, more hours worked per week, more nights on call per month, working in public hospitals, psychological morbidity, high levels of job stress, low levels of job satisfaction, and poor doctor-patient relationships. Factors independently associated with psychological morbidity included lower income, more nights on call per month, working in enterprise-owned hospitals, burnout, high levels of job stress, and low levels of job satisfaction. Conclusions: Burnout and psychological morbidity are common in Chinese neurologists. Burnout is the single greatest predictor of neurologists' psychological morbidity, high job stress, and low job satisfaction.